OZONE - THE LATEST ADVANCE IN STERILIZATION OF MEDICAL DEVICES - Murphy, Lorna (Operating Room Nurses Association of Canada Journal, 2006)
How many times have procedures in your operating rooms been delayed because the instruments needed were still in the sterilizer? As Perioperative nurses you are likely to be quite familiar with the constant pressure to ensure that scarce instrumentation is available when needed. In 2003, a Canadian company developed a unique sterilization process employing ozone as the sterilizing agent. This technology is a safe, rapid and economical alternative to other low temperature sterilization modalities and may relieve some of the pressure experienced when instruments in short supply are in high demand. This article will discuss the principles of the sterilizer and the cycle and will explore the advantages of using this sterilization technology.